Ferrous Sulphate-Induced Black Color Discoloration of Teeth: A Case Report - Rawal, Kala Bahadur; Girish, H.N.; G.J, Andrew; Anusha, S.; Luhar, Min Bahadur (Journal of Pharmacy Practice and Community Medicine)
Introduction: Several medications will lead to dental discoloration. Black color teeth discoloration is due to iron ferric salts and more commonly ferric sulfide and the exact mechanism for tooth staining due to iron salt is unknown. Still, this evidence is more common with the liquid iron supplement exposure used for the prevention and management of anemia. Case presentation: A 16-year-old female patient admitted to a female general medicine ward with complaints of black color teeth discoloration for one month, fever insidious in onset for three days, breathlessness and dry cough for three days and loose stool three episodes per day since three days. She was a known case of Chronic Kidney Disease since the age of 18 months and on regular medication. No significant family history was present. On Examination, The patient was having black color teeth discoloration BP-110/70mm of Hg, PR-104bpm and SPO2-98%). On lab Investigation, her blood test revealed (Hb-6.5gm/dl) and Scr 5mg/dl and S. Urea is 127mg/dl, Sodium- 131mEq/L hence diagnosed as Acute Gastroenteritis with Urinary Tract Infection and CKD major with severe anemia and with mild Right hydroureteronephrosis due to bladder outlet obstruction. Treatment: She was treated with Inj. Ciprofloxacin 400mg IV Twice daily, Inj. Metronidazole 500mg IV Thrice daily, Inj. Ceftriaxone 1g IV Twice daily, Tab. Ferrous sulfate + folic acid (IFA) 335+0.5mg PO Twice daily, Tab. Folic Acid 5mg PO Once daily, Tab. Calcium Carbonate + D3 500mg PO Once daily, Tab. Sodium bicarbonate 200mg PO Thrice daily, Syrup Dextromethorphan + Chlorpheniramine + Phenylephrine 10ml Thrice daily. Conclusion: The patient was in the long run (18 months) therapy of iron supplement. The teeth discoloration was developed due to the chronic toxicity of iron supplement (Ferrous sulfate). The iron-rich diet was recommended for the patient and the sulfate salt of iron changed to fumarate salt.
Keywords: Anemia; Iron; Staining; Adverse drug reactions; Sulfate salts; Drug-induced disorders